2019
DOI: 10.4103/tcmj.tcmj_89_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intramuscular methylergometrine, rectal misoprostol, and low-dose intravenous oxytocin in active management of the third stage of labor

Abstract: Objective: Active management of the third stage of labor (AMTSL) is a critical intervention for the prevention of postpartum hemorrhage (PPH), which is still the most common cause of maternal morbidity and mortality worldwide. The objective of the study is to compare the effect of intramuscular methylergometrine, rectal misoprostol, and low-dose intravenous oxytocin in the AMTSL in terms of amount of blood loss and duration of the third stage of labor, cost-effectiveness, and side effect profile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Various medical protocols are developed to prevent bleeding after surgical abortion or labor. However, these protocols are continuously modified to achieve better outcomes and higher success rates [ 31 – 33 ]. Even though there is no significant difference regarding the severity of bleeding in the three groups in our study, those given misoprostol plus methylergonovine showed mild bleeding compared to the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Various medical protocols are developed to prevent bleeding after surgical abortion or labor. However, these protocols are continuously modified to achieve better outcomes and higher success rates [ 31 – 33 ]. Even though there is no significant difference regarding the severity of bleeding in the three groups in our study, those given misoprostol plus methylergonovine showed mild bleeding compared to the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study methyl ergotamine was found to be more effective but had more side effects as well. 8,16,17 In a study done by Megha and colleagues misoprostol was found to be more effective in reducing blood loss as compared to Oxytocin and Meth ergotamine . 18 Various studies performed across the globe point towards difference in results.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of herbs have been found for treating gynecological diseases, such as irregular menses and heavy menstrual bleeding. Though studies have shown the beneficial effects of herbs on heavy menstrual bleeding, there is no comprehensive study on the effectiveness of herbs used for treating abnormal uterine bleeding [ 6 ].…”
Section: Introductionmentioning
confidence: 99%